High-Pathogenicity Island of Yersinia spp. in Escherichia coli Strains Isolated from Diarrhea Patients in China - Xu, Jian-guo (American Society for Microbiology, 2000)
The high-pathogenicity island (HPI) of Yersinia has been observed in 93% of 60 enteroadhesive Escherichia coli strains and 80% of E. coli strains isolated from blood samples. In the present study we investigated 671 fecal samples from patients with diarrhea in Shandong Province, China, and isolated HPI-harboring E. coli from 6.26% of the samples. The isolation rates for patients with diarrhea in three age groups, 10 to 20, 30 to 40, and 50 to 60 years, were 6.70, 12.35, and 10.81%, respectively. Therefore, HPI-harboring E. coli is the third most frequently isolated enteric pathogen from patients with diarrhea. Vomiting and abdominal pain were recorded for 33.33 and 66.67% of the patients, respectively. Stools with blood were observed for 9.52% of the patients. Twenty-four of 42 (57%) patients experienced a temperature over 37.4°C. These observations indicate that HPI-harboring E. coli is one of the major causes of diarrheal disease in China and that the clinical symptoms caused by HPI-harboring E. coli differ from those caused by enteroadhesive E. coli.